2007
DOI: 10.1110/ps.072975107
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the structure and dynamics of phospholamban pentamer in its unphosphorylated and pseudo‐phosphorylated states

Abstract: Human phospholamban (PLN), a 30 kDa homopentamer in the sarcoplasmic reticulum (SR) membrane, controls the magnitude of heart muscle contraction and relaxation by regulating the calcium pumping activity of the SR Ca 2+ -ATPase (SERCA). When PLN is not phosphorylated, it binds and inhibits SERCA. Phosphorylation of PLN at S16 or T17 releases such inhibitory effect. It remains a matter of debate whether phosphorylation perturbs the structure of PLN, which in turn affects its interaction with SERCA. Here we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
3
23
0
1
Order By: Relevance
“…The PLB-PLB FRET max parameter, a measure of the probe separation distance, did not change with pseudo-phosphorylation indicating the quaternary structure was unaffected. These results are consistent with a recent NMR study that observed no significant changes to short-range distance constraints with the S16E mutation (19). According to a computational model of intrapentameric energy transfer based on ring-oligomer FRET theory (29), the average nearest-neigh-…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The PLB-PLB FRET max parameter, a measure of the probe separation distance, did not change with pseudo-phosphorylation indicating the quaternary structure was unaffected. These results are consistent with a recent NMR study that observed no significant changes to short-range distance constraints with the S16E mutation (19). According to a computational model of intrapentameric energy transfer based on ring-oligomer FRET theory (29), the average nearest-neigh-…”
Section: Discussionsupporting
confidence: 92%
“…To test whether phosphorylation stabilizes a compact pentamer conformation, we obtained distance constraints by measuring fluorescence resonance energy transfer (FRET) between N-terminal fluorescent protein fusion tags. In this study, we mimicked phosphorylation of PLB by PKA and CaMKII with glutamate substitutions at positions 16 and 17 (18,19). The extent to which glutamate substitutions recapitulate phosphorylation of PLB is not known.…”
Section: Phospholamban (Plb)mentioning
confidence: 99%
“…If the subunits in a complex are identical, then the complex is called homo-oligomer; otherwise hetero-oligomer. For example, the sodium channel is formed by a monomer [192] while the potassium channel by a homo-tetramer [88]; the phospholamban is formed by homo-pentamer [93,193] while the Gamma-aminobutyric acid type A (GABAA) receptor by a hetero-pentamer [84,194]; the M2 proton channel is formed by a homo-tetramer [87] while hemoglobin by a hetero-tetramer [195].…”
Section: Quatidentmentioning
confidence: 99%
“…Therefore, the final predicted result should be determined by a fusion approach through the following voting mechanism. According to eq 11, the voting score for the query protein P belonging to the ith class is given by 2,3,4,5,6,7,8,10,12) (12) where i ) 1 is for monomer, i ) 2 for dimer and so forth, w K 1 and w K, 2 are the weight factors and were set at 1 for simplicity, thus the query protein P is predicted belonging to the class or subset for which the score of eq 12 is the highest; i.e., 2,3,4,5,6,7,8,10,12) …”
Section: Optimized Evidence-theoretic K Nearest Neighbormentioning
confidence: 99%
“…If there is a tie among two or more classes, then the final predicted result will be randomly assigned to one of their corresponding classes although this kind of tie case rarely happens and actually was not observed in the current study. By changing (i ) 1, 2, 3,4,5,6,7,8,10,12) to (i ) homo, hetero) and working on the subclass benchmark data set (cf. eq 2 and the Supporting Information B), eqs 11 and 13 can be automatically used to solve the second-level problem, that is, identify the half-query protein P (which has already been identified as an oligoprotein in the first-layer prediction) belonging to a homo-oligomer or hetero-oligomer.…”
Section: Optimized Evidence-theoretic K Nearest Neighbormentioning
confidence: 99%